Molluscan mechanosensory neurons: Structure and, following injury, the process of recovery. - Steffensen, Isabella. (University of Ottawa (Canada), 1995)
Examination of Aplysia californica's defensive withdrawal reflexes has been particularly powerful in understanding learning-related phenomena. The tail withdrawal reflex is mediated in large part by identified tail mechanosensory neurons in the pleural ganglia. Although learning-induced changes at the synapses between the identified tail mechanosensory neurons (MSNs) and their follower motor neurons have been extensively studied, the peripheral sensory endings have not been characterized. Using a combination of immunohistochemistry (with an antibody to a neuronal-specific tubulin) and electron microscopy, putative mechanosensory structures in the tail region were identified. These neural structures penetrated the epithelium and terminated as endings consisting of mixed cilia and microvilli. Brunet et al. (1991, Science 252:856) have identified a peptide, sensorin-A, that is specific for the Aplysia MSNs. To determine if the cilia/microvilli endings were the sensory endings of the MSNs, immunostaining for sensorin-A was performed in the tail region. Sensorin-A immunofluorescence did not colocalize with the ciliated/microvillar sensory structures, but did reveal the endings of the MSNs. Confocal microscopy of the sensorin-A fibers revealed that they terminated as coiled structures deep in the body wall. The general morphology of these endings most resembled that of vertebrate muscle spindles. Although the ciliated endings were determined not to be associated with the sensorin-A MSNs, it is possible that they are the unidentified low-threshold mechanoreceptors for which there is physiological evidence. Electrophysiological experiments (Brunet et al., ibid) suggest that sensorin-A acts as a neurotransmitter centrally. In the periphery sensorin-A immunofluorescence was localized predominantly to varicosities in the MSNs. Immunogold electron microscopy revealed that at the ultrastructural level, sensorin-A was localized mainly to dense granules, and dense-core vesicles, a distribution consistent with a neuroactive peptide. Sensorin-A's presence peripherally raises the possibility of a parallel with substance-P, a neuroactive peptide released at primary afferent terminals of vertebrate nociceptors. The mechanoafferents that innervate the tail are carried from the ganglia to the tail region in nerve p9. To determine if the tail MSNs have the ability to regenerate, bilateral crushes of nerve p9 were performed. Regeneration was monitored morphologically using immunostaining for sensorin-A, and behaviourally by examining the tail withdrawal reflex. Functional recovery, indicated by a return of the tail withdrawal reflex, was observed between 10 and 15 days, and growth of sensory fibers (as observed by sensorin-A immunostaining) down p9 paralleled the time course for behavioural recovery. Recently, the pond snail Lymnaea stagnalis has emerged as a model system for studying rhythm generation. Nothing is however known about the mechanosensory inputs that affect behaviours such us respiration, locomotion and feeding. Sensorin-A immunostaining on the Lymnaea CNS, and in situ hybridization with a probe to the sensorin-A gene of Aplysia, revealed putative mechanosensory neurons. These putative sensory cells did not colocalize with previously identified motor neurons, interneurons or neurosecretory cells. As would be expected for a mechanoafferent, sensorin-A positive fibers were found in nerve tracts innervating the body wall.
Keywords: Biology, Neuroscience.